The Stability and Growth Pact: enforceable, flexible or dead? - Vila Maior, Paulo (2010)
The paper reflects the nature of the Stability and Growth Pact capturing its innovative essence as a ‘more-than-federal’ device, following an alternative classification I propose. This classification is based on a comparative method using other countries as case studies, seeking their main characteristics when the rules of fiscal discipline states have to comply with are concerned. Then the attention shifts to a highly sensitive question – whether enforceability of the Stability and Growth Pact is the expected outcome. This is an important discussion since recent debates on the desirability to make the pact more flexibility fuelled intense controversy among scholars, member states and supranational institutions. Also recent events showing how key member states are unable to respect the rules of the pact feed further doubts about its strict implementation. Using several scholars’ judgment that the pact’s main shortcoming is its rigidity, the question is to know whether the pact is geared towards enforceability without any variation that undermines its original meaning. The methodology uses three types of sources. On the one hand, a literature review emphasising the main theoretical conclusions that emerge on this issue. On the other hand the results of interviews carried over at the Commission, the European Central Bank and a sample of nine member states at the level of Finance and Foreign Affairs ministries. Some divergence is found between the solutions devised by academics and the answers given by practitioners. This gap is heightened by the third methodological element: an examination of national governments’ recent performance in terms of fiscal discipline, as well as the reaction of the Commission. This is a crucial task for concluding about the likely fate of the Stability and Growth Pact.